Competences in focus: Rural Extensionist, a multifunctionality profession (Research, Society and Development, 2021)
The literature presents countless works that talk about diverse attributions and possible training of rural extension agents. The present work sought to clarify the demands of the current attributions listed in the extensionists, and to answer what are the current updates postulated to the professionals of Rural Extension. The methodological option chosen was a bibliographic narrative review that involves the theme and dialogues with a pointed problem, analyzing theses, dissertations and scientific articles. All material was read, categorized and critically analyzed. This document helps to explain the historical trajectory of Rural Extension and its conclusions on the behavior of extension agents and sought to understand how institutionalized demands in the exercise of their functions. As a result, was possible have a perception that multifunctionality is a characteristic inherent to the profession of extensionists. As an agent for the implementation of public politics, the theory that defines street-level bureaucrats glimpses the importance of the rural agent executing government programs. Even though Rural Extension professionals were guided only by regulations, the reality of the field in such a diverse and dynamic Brazil, does not allow demanding such multifunctionality from this professional, fact that requires the formation of multidisciplinary teams, since the contribution of an extension agent it can be complemented by the training of other. Regarding the new conditions in face of the global health crisis, a remote ATER gives rise to a new portfolio of skills, and it is necessary that future studies also address evaluations on these competencies.